Обеспечение сбалансированности бюджетной системы Украины - Усков, И.В. (Культура народов Причерноморья, 2014)
Запропоновані комплексні заходи щодо забезпечення збільшення доходів і оптимізації витрат
місцевих бюджетів, розвитку системи міжбюджетних відносин, економічного потенціалу
територіальних утворень. Розроблена теоретична модель збалансованості місцевих бюджетів України
в умовах становлення програмно-цільового методу планування на місцевому рівні, впровадження
обґрунтованої системи оцінки якісного виконання бюджетних програм. Запропоновані комплексні
заходи щодо забезпечення ефективної реалізації бюджетної політики на місцевому рівні. Предложены комплексные мероприятия по обеспечению увеличения доходов и оптимизации
расходов местных бюджетов, развития системы межбюджетных отношений, экономического
потенциала административно-территориальных образований. Разработана теоретическая модель
сбалансированности местных бюджетов Украины в условиях становления программно-целевого метода
планирования на местном уровне, создания обоснованной системы оценки качества исполнения
бюджетных программ. Предложены комплексные мероприятия по обеспечению эффективной
реализации бюджетной политики на местном уровне. Complex measures are offered on providing of increase of profits and optimization of charges of
local budgets, development of the system of interbudgetary relations, economic potential of territorial
educations. The theoretical model of balanced of local budgets of Ukraine is worked out in the conditions of
becoming of programmatic-having a special purpose method of planning at local level, creation of the
reasonable system of estimation of quality of execution of the budgetary programs. Complex measures are
certain on providing of realization to the fiscal policy at local level. The system of estimation of management
quality is worked out by local finances, increase of efficiency of realization of fiscal policy, strengthening of
fiscal decentralization of administrative-territorial educations. For Ukraine at local level certain direction on
optimization of the system of local taxation, increases of efficiency of the system of interbudgetary relations,
creation of effective mechanism of the budgetary adjusting. Coming from positive foreign experience measures
are certain on providing of balanced of the budgetary system of Ukraine.